2010
DOI: 10.1186/1471-2350-11-94
|View full text |Cite
|
Sign up to set email alerts
|

Association of the genetic polymorphisms of the ACE gene and the eNOSgene with lupus nephropathy in northern Chinese population

Abstract: BackgroundIt has been reported that some single nucleotide polymorphisms (SNPs) of the angiotensin converting enzyme (ACE) gene and the endothelial nitric oxide synthase (eNOS) gene are associated with the development of systemic lupus erythematosus (SLE) and the progression of nephropathy. The aim of this study was to evaluate the possible association between six SNPs (A-5466C, T-3892C, A-240T, C1237T, G2215A and A2350G) of the ACE gene and two SNPs (T-786C and G894T) of the eNOS gene with lupus nephropathy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 38 publications
(40 reference statements)
0
22
0
Order By: Relevance
“…The eNOS polymorphisms have been associated with SLE by some authors, but by no means all [5][6][7][8][9][10][11][12], which may be due to small sample sizes, low statistical power, and/or clinical heterogeneity. Therefore, in order to overcome the limitations of individual studies, resolve inconsistencies, and reduce the likelihood that random errors are responsible for false-positive or false-negative associations, we turned to meta-analysis [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The eNOS polymorphisms have been associated with SLE by some authors, but by no means all [5][6][7][8][9][10][11][12], which may be due to small sample sizes, low statistical power, and/or clinical heterogeneity. Therefore, in order to overcome the limitations of individual studies, resolve inconsistencies, and reduce the likelihood that random errors are responsible for false-positive or false-negative associations, we turned to meta-analysis [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of an association between the T-786C SNP and autoimmune diseases in the present study could be due to the predominance of the T allele within the Kuwaiti population. Table 4 shows data from different population studies in Kuwait [24], China [26,27], Columbia [28] and the USA [29] that also failed to find a significant association between the T-786C SNP and SLE, suggesting that it is unlikely to be a genetic susceptibility factor for SLE. Association of the T-786C SNP with HT has yet not been reported in any population study.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Lupus nephritis is characterized by increasing vascular lesion risk, 13 and some studies have found that the ACE polymorphism was associated with lupus renal involvement. 10,14 In contrast to these diseases, there is no study thus far that has analyzed the ACE polymorphism in DM, a disease that involves vascular pathogenesis mediated by humoral processes with secondary ischemic changes of muscle fibers. 1,2,31,32 In these conditions, abnormalities have been found in the endothelium of capillaries, arterioles, and veins, which have been suggested to represent primary disease-related alterations.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Nevertheless, to our knowledge, no studies to date have analyzed the ACE gene polymorphism in DM. Moreover, this polymorphism could be an attractive candidate among the factors that play a role in the development of vascular pathological and systemic inflammatory states; therefore, contributing to DM susceptibility and/or DM pathogenesis.…”
Section: Introductionmentioning
confidence: 99%